Relationship Between Autophagy and Metabolic Syndrome Characteristics in the Pathogenesis of Atherosclerosis - Xu, Jing; Kitada, Munehiro; Ogura, Yoshio; Koya, Daisuke (Frontiers in Cell and Developmental Biology, 2021)
Atherosclerosis is the main cause of mortality in metabolic-related diseases, including cardiovascular disease and type 2 diabetes (T2DM). Atherosclerosis is characterized by lipid accumulation and increased inflammatory cytokines in the vascular wall, endothelial cell and vascular smooth muscle cell dysfunction and foam cell formation initiated by monocytes/macrophages. The characteristics of metabolic syndrome (MetS), including obesity, glucose intolerance, dyslipidemia and hypertension, may activate multiple mechanisms, such as insulin resistance, oxidative stress and inflammatory pathways, thereby contributing to increased risks of developing atherosclerosis and T2DM. Autophagy is a lysosomal degradation process that plays an important role in maintaining cellular metabolic homeostasis. Increasing evidence indicates that impaired autophagy induced by MetS is related to oxidative stress, inflammation, and foam cell formation, further promoting atherosclerosis. Basal and mild adaptive autophagy protect against the progression of atherosclerotic plaques, while excessive autophagy activation leads to cell death, plaque instability or even plaque rupture. Therefore, autophagic homeostasis is essential for the development and outcome of atherosclerosis. In this review, we discuss the role of autophagy and metabolic syndrome in the pathogenesis of atherosclerosis and potential therapeutic drugs that target these molecular mechanisms.